Primary care physicians: The silent architects of a diabetes-safe future - Neelesh Kapoor; Raman Kumar (Journal of Family Medicine and Primary Care)
This editorial underscores the indispensable role of primary care physicians in addressing the diabetes epidemic. Amid global advances and digital shifts, the family physician remains the bedrock of detection, continuity, and contextual care. Empowering primary care with resources, training, and policy support is crucial for equitable, effective diabetes management—especially in low-resource settings.